Design and Optimization of an Outer Rotor Spoke Type PMSM With Improved Saliency for a Lightweight Racing Vehicle - Karatepe, Hasan Can; Tekgun, Burak; Tekun, Diclem; Tekgun, Didem (IEEE, 2024)
This paper presents the design and optimization of an outer rotor spoke-type permanent magnet synchronous motor, aimed at achieving high torque density. The improvement is accomplished by enhancing the saliency through a center shift of the rotor arc, while simultaneously minimizing cogging torque and torque ripple. The proposed design is optimized for an electro-mobile that will participate in TEKNOFEST's "Efficiency Challenge". A vehicle dynamics simulation with the parameters of the designed vehicle was done under the "New European Driving Cycle" (NEDC) to determine the required torque and speed values using MATLAB's "Virtual Vehicle Composer" application. The multi-objective differential evolution (MODE) algorithm was chosen for optimization and further altered for maximum torque per ampere (MTPA) angle sweep, since each optimization individual would have a different MTPA angle. The optimization was conducted with 40 generations and 522 individual designs. An optimal solution from the Pareto-Front was selected and its performance was investigated using the 2D finite element analysis (FEA).
Keywords: PMSM; Hub Motor; Spoke Type IPM; Mode Optimization; Saliency